Реалізація принципу комунікативної аґональності на матеріалі діалогу Лесі Українки «Три хвилини» - Стародубцева, Любов; Starodubtseva, Lubov (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті досліджено особливості побутування античного принципу аґональної комунікації, його реаліза-цію в діалозі Лесі Українки «Три хвилини». Модерна аґональність у творі проявляється на всіх рівнях художнього тексту. У розвідці доведено, що провідною рисою комунікації у діалозі «Три хвилини» є аґон. The article studies the pequliarities of existing of the antique principle of agonal communication, it’s realization in Lesya Ukrainka’s dialogue “Three minutes”. In the text there are all the immanent components of agon as a means of communication (periods of agon’s development are kept up, there is a conflict of interests, aggression to the rival, ambitiousness of the opponents). However the components’ authour’s modification gives a modern sound to the classic form. Agon appeares on all the levels of the literary text. Antagonists’ verbal fight has a continuous character, it simultaneousely contains features of discussive and confrontative agons. The article proves that the main feature of communication Lesya Ukrainka’s dialogue “Three minutes” is the agon, which continues even after the formal ending of the dispute.
Realization of the Principle of Communicative Agon on the Material of Lesya Ukrainka’s Dialogue “Three Minutes”
Keywords: аґон; комунікація; діалог; вербальна битва; суперечка; agon; communication; dialogue; verbal battle; dispute